Proceedings of the 2nd Sari Mulia International Conference on Health and Sciences 2017 (SMICHS 2017) 2017
DOI: 10.2991/smichs-17.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Of Physical Activity, Diet, And Age Menarche With Age Menopause At Elderly Posyandu Working Area Puskesmas Pekauman Banjarmasin

Abstract: Objective: To know the relationship of physical activity, diet and menarche age with age of menopause at Posyandu elderly working area Puskesmas Pekauman Banjarmasin. Methods:The research used quantitative analytic with cross sectional approach. The population is women aged 45-59 years in Posyandu elderly working area Puskesmas Pekauman. Samples were post-menopausal women aged 45-59 at Posyandu elderly working area Pekauman Community Health Center April 2017 amounted to 47 people, taken by accidental sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Physical activity was influenced by the women's age, place of residence, education level, occupation, marital status, body mass index (BMI), parity and socioeconomic status (4,28). This result is consistent with that of previous studies that observed moderate physical activity among the participants (6,9,29). By contrast, other studies observed sedentary physical activity and poor diet among their study participants (30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Physical activity was influenced by the women's age, place of residence, education level, occupation, marital status, body mass index (BMI), parity and socioeconomic status (4,28). This result is consistent with that of previous studies that observed moderate physical activity among the participants (6,9,29). By contrast, other studies observed sedentary physical activity and poor diet among their study participants (30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 93%
“…A healthy diet can reduce the risk of diseases and enhance quality of life (34). Moreover, adequate nutritional fulfillment can considerably reduce the negative consequences of menopause (29). The results of the present study revealed that more than half of the participants ate refined food items once a month or less, dined out less than once a month, ate three meals a day and ate ghee, butter, cream, and mayonnaise once a month or less.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations